Pathologic function and therapeutic potential of extracellular vesicle miRNA in sepsis - Deng, Rou; Cui, Xiayu; Zhang, Runze; Liu, Changya; Luo, Jielian; Liu, Liang; Zhang, Wen; Fang, Bangjiang (Frontiers in Pharmacology, 2024)
Sepsis is a systemic inflammatory response initiated by an infection, which can lead to multi-organ dysfunction. The pathophysiology of sepsis is complex, and treatment options are limited. Traditional antibiotic therapies have shown limitations, such as promoting the emergence of antibiotic-resistant bacteria and disrupting the natural microbiota. Consequently, there is a pressing need to explore diverse therapeutic approaches for sepsis management. Extracellular vesicles, which play a crucial role in cell-to-cell communication, are released by various cell types throughout the body and possess a membrane structure composed of a lipid bilayer.MicroRNAs may be encapsulated within these structures and can be selectively delivered to target recipient cells through the activation of cell surface receptors or via endocytosis and fusion, thereby modulating the biological functions of target cells.The article examines the pathological alterations that happen as sepsis progresses and the biological control of extracellular vesicles and microRNAs in sepsis. This review focuses on the role of extracellular vesicles and their microRNAs on controlling the inflammatory response, macrophage polarization, programmed cell death, endothelial dysfunction, and microcirculatory changes in sepsis. Furthermore, the obstacles encountered by this novel therapy are also examined.